Protein Immobilization On Glutaraldehyde Activated Nylon Membranes- Effects Of The Activation Condition - Halil, Nur Hafizah Abd (Universiti Sains Malaysia, 2017)
Protein immobilization on glutaraldehyde (GA) activated nylon membranes has been studied in this work. Nylon membranes was first activated with GA and then immobilized with the protein. The morphology of the membranes was characterized by scanning electron microscopy (SEM), FTIR analysis and thermogravimetric analysis (TGA) to check the presence of glutaraldehyde. The preliminary study was carried out to investigate the effect of three factors (incubation time, pH and concentration of GA) on protein binding while the membrane sample is fixed to 16 wt% of nylon polymer and 84 wt% of mixture solvent and non-solvent. From the study, it can be found that the optimum condition of GA-activation which are incubation time is at 40 min, at pH 7.5 and 1 wt% of GA concentration. Since the mixture factors (concentration of polymer and mixture solvent and non-solvent) and process factors (incubation time and pH) were inter-related, therefore Design of Experiment (DoE) was applied. The optimum GA-activation conditions was obtained from a crossed mixture-process design methodology (Design of Experiment) at 25 wt% of nylon polymer, 75 wt% of mixture solvent and nonsolvent, GA solution at pH 9.0 and GA activation time of 70 min, with protein binding predicted at 2410.19 μg/cm3. The experimental validation was conducted at this optimum condition and the protein binding result was found at 2411.57 μg/cm3 with the standard deviation of 0.057%. The experimental result shown a small standard deviation which means the model can be used further to predict the protein that immobilized on glutaraldehyde activated nylon membranes.